State support measures for import substitution impact on the investment projects efficiency in the power industry - E. A. Tregubova; A. I. Tregubov (Вестник университета)
In the structure of thermal generation of the Russian Federation, the share of modern combined-cycle plants, characterized by low specific fuel consumption (CCGT), is only 16 % and is based on the use of Western-made gas turbines. To stimulate import substitution, as measures of state support, special prices for capacity produced by new generation are used, and tax incentives are provided to investor enterprises. The paper assesses the impact of existing state support measures on the commercial efficiency of the investment project for the construction of a CCGT-120 on Russian equipment in the city of Saki (Republic of Crimea). The indicators of net present value (NPV), internal rate of return (IRR) and payback period for three scenarios (basic and two alternative, differing in the composition of state support measures) are considered. It is shown that the use of a special capacity tariff for new generation (competitive capacity extraction of new generating facilities – KOM NG) and tax incentives ensures the project’s profitability at the level of 18.7 % and the payback period is 7 years. Refusal to provide special tariffs for the capacity will cause the project to become unprofitable. The abolition of tax incentives will lead to a reduction in NPV by 40 %, a decrease in the project’s profitability to a critical level of 14.7 % and an increase in the payback period by 2 years. In order to rise the commercial efficiency of investment projects for the installation of CCGT units on Russian equipment and reduce the scale of their state support, it is necessary to increase the volume of heat supply and optimize investment costs.